Prototype Monitoring Otomatis Alat Pemberi Makan Dan Minum Ayam - Laksantika, Dimas; Nugroho, Atmoko (Jurnal Pengembangan Rekayasa dan Teknologi, 2022)
There are problems faced by chicken farmers, namely how to improve chicken yields so that it will impact on improving the welfare of members of chicken farmers. One of them is how chicken feed can be routinely and scheduled. Currently the method used for chicken feed is by manual means of sprinkling chicken feed / pellets routinely both morning and evening, so that it has an obstacle that is sometimes the chicken breeder is forgetful or late in feeding the chicken so that it will affect the growth of the chicken. This can result in late harvest days and yields are not optimal because the chicken weight is not optimal. The purpose and objective of this activity is to obtain an appropriate technology design for making chicken feed equipment automatically so that chicken feed can be carried out routinely and on a scheduled basis. The results of this activity are obtained the design of appropriate automatic chicken feed tools to help overcome the problems of chicken farmers in increasing chicken yields. It is expected that the chicken yield will be increased later than when feeding chicken is done manually.
Keywords: Eating and Drinking; Chicken; Automatic; Monitoring; Arduino